Synthesis and Characterization of ZnO/Poly(methyl methacrylate) Composites by in situ Polymerization - Li, Meng; Wang, Yan; Yang, Benhong (Asian Journal of Chemistry, 2012)
A simple approach for in situ preparation of transparent ZnO/poly(methyl methacrylate) nanocomposite films was developed. Scanning electron microscope images revealed that zinc oxide nanocrystals were homogeneously dispersed in poly(methyl methacrylate) matrix. The TGA and ultraviolet-visible absorption measurements displayed that ZnO/poly(methyl methacrylate) nanocomposite films possessed better thermal stability and optical property than pristine poly(methyl methacrylate) films.